АПСУРДОТ И ПОБУНАТА ВО РОМАНОТ ПУСТИНА ОД ЃОРЃИ АБАЏИЕВ - Гоце Смилевски (Институт за македонска литература во Скопје, УКИМ Скопје, 2024)
The text is an attempt to interpret the novel Desert by Gjorgi Abadijev through some of the basic concepts of the philosophy of existentialism, more precisely through the premises presented in The Myth of Sisyphus by Albert Camus. The analysis of the novel focuses on comparing the ways in which the two main characters, Gligor and Arso, both sentenced to a life imprisonment, accept (or are unable to accept) the absurdity of existence, rely on hope or reject it with contempt, strive for freedom or give it up as something unattainable, choose life or death. The text thus indicates that Abadziev’s novel was created in the context of existentialist trends in literature, current in the European culture at the time when Desert was written.
Keywords: Gjorgji Abadziev; Albert Camus; Sisyphus; absurd; rebellion; suicide